If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6x-8)=(5x+14)
We move all terms to the left:
(6x-8)-((5x+14))=0
We get rid of parentheses
6x-((5x+14))-8=0
We calculate terms in parentheses: -((5x+14)), so:We get rid of parentheses
(5x+14)
We get rid of parentheses
5x+14
Back to the equation:
-(5x+14)
6x-5x-14-8=0
We add all the numbers together, and all the variables
x-22=0
We move all terms containing x to the left, all other terms to the right
x=22
| 1/6x-(1/7x)+1/42x=6 | | -(v-4)=-6v+16 | | 79.8=7(m+3.8 | | 2n-7n=16 | | -2x+4=-2x+6 | | 3x+38+5x-32=180 | | 7x-(6)=36 | | -10(-2)+y=4 | | 1=-3w+64 | | -106+3x=38+9x | | 285=19n | | 48n+28=0 | | -6x+7x-8x=0 | | (3x-5)+(2x-25)=180 | | .15+.05x=1.05 | | 0.4h-3=-1 | | (w)/(5)-((w+3))/(w)=-(3)/(w) | | |y|+10=14 | | 2/3z=4.1/4 | | 19=19s | | -119+2x=-5x+42 | | 6h^2+4h=6h^2+4h | | -16w+4=-30w-48 | | 13v-9v=12 | | (3x+30+24)=90 | | 2.4w+2.6=23 | | 5t-11=13-t | | 5(n)=5(11)*5(3) | | 6a-5+2=5a-7+a | | 0.09*x+x=218 | | 2u-8=-12 | | 5t-11=-4t |